Initiation to teaching in Physical Education: bibliometric review of knowledge production in scientific journals - Soares da Silveira, Isabella (2024)
This bibliometric review aims to analyze the production of knowledge on the initiation of teaching in Physical Education conducted through an Institutional Program. The articles were searched in electronic databases and 18 articles were found, published in nine scientific journals. The analysis showed that few journals in Physical Education and other areas of knowledge have published on the topic and the population in focus. The publications on PIBID Physical Education began in 2014, with an increase between 2017 and 2019, followed by a decline from 2020 onwards. There was a shortage of authors who consistently studied the theme as their primary object of research. There was also a predominance of studies developed in the South, especially at the Universidade Federal de Santa Maria. Furthermore, the pedagogical axis and keywords PIBID, training and Physical Education were highlighted, along with a predominance of qualitative methodological design in scientific dissemination.